Fiscal Institutions and the Size and Inter-Regional Distribution of Public Redistribution - Ponce Rodríguez, Raúl Alberto (2018)
Fiscal institutions, which are responsible for the delegation of tax and spending powers among different tiers of governments, are important determinants of the size and efficiency of public redistribution. In this paper we develop a comparative analysis of the impact of fiscal decentralization vis-à-vis tax revenue sharing on the government’s effort to redistribute income. The main findings are: first, the size of the national budget for public redistribution is the same under fiscal decentralization and tax revenue sharing. Second, different fiscal institutions lead to different regional distributions Third, when choosing between decentralization and tax revenue sharing, there is a tradeoff between the efficiency and the regional effort of the government to redistribute income.